First Total Synthesis of Murrastifoline B and an Improved Route to Murrastifoline F - Börger, Carsten; Schmidt, Arndt W.; Knölker, Hans-Joachim (Synlett, 2014)
We report the first total synthesis of murrastifoline B and an improved route to murrastifoline F using a twofold palladium-catalyzed Buchwald–Hartwig amination as key step. The monomeric carbazole and the biaryl precursor are also prepared via palladium-catalyzed coupling reactions.
Keywords: alkaloids; catalysis; cyclization; natural products; palladium